Parenting Practices Osing Parents and Their Contribution to Adolescent Mental Health Promotion - Ricka Ayu Yuliyasari; Novita Surya Putri; Leni Anggraini; Ani Firda; Sholihin Sholihin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Adolescents are vulnerable to mental disorders because adolescent phase is a turbulent period of adjustment to adulthood. The choice of parenting patterns adopted by parents is important for teenagers in maintaining their mental health, to survive the social problems and psychological stress experienced. In the Osing tribe's parenting pattern by obeying the rules and supervision of parents and balanced with the freedom given to children by applying disciplinary and cultural values. Osing adolescents have higher assertive abilities compared to other ethnic groups, they can manage anticipatory problems without emotions. This study aims to explore the parenting patterns of Osing parents in building adolescent mental health. The design used in this study was qualitative with a phenomenological approach. By involving 6 participants, namely parents of teenagers from the osing tribe and native residents of Kemiren Village. Participants were selected using purposive sampling, which involves determining the sample based on relevant criteria. The research was conducted with formal semi-structured interviews. using data analysis techniques with the colaizzi method, through the process of collecting, transcribing and analyzing data. In the data analysis stage, using NVIVO 12 software programming. In the research that has been conducted, 2 themes and 4 sub-themes were identified, the themes identified were nurturing culture and trust. Osing parents build character in adolescents by introducing the culture and arts of the Osing tribe. There is no coercion from parents in participating in art activities and in decision making, adolescents are always given support and motivation with two-way communication. Teenagers are accompanied in training activities and facilitated in art activities. Osing parents believe that by having one child they can focus on caring for children, especially in the adolescent phase which requires extra attention.